Wyniki operacyjnego leczenia dorosłych chorych z jednostronnym niedowładem mięśnia skośnego górnego - Kaczmarek, Beata (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Purpose: The purpose of this study was to determine the outcomes of surgical management in adult patients with unilateral superior oblique muscle palsy. Material and methods: A retrospective review of 82 patients who underwent surgical correction at the Department of Strabismology, Cracow Eye Hospital over a 20 years period (1982-2003) was done. The patients were divided into 2 groups: congenital (group I) and acquired (group II) of superior oblique muscle palsy. Group I consisted of 43, group II of 39 patients. The mean age at surgery was 34 years in the congenital and 38 years in the acquired group. Preoperative and postoperative vertical deviation and excycloduction was measured in diagnostic positions of gaze using a major synoptoscope. Results: There were a total of 97 operations: inferior oblique muscle recession was performed in 61 patients, superior oblique muscle tuck in 33, contralateral inferior rectus muscle recession in 1 patient, superior rectus muscle recession in 1 patient and inferior rectus muscle resection in 1 patient. 83% of patients underwent muscle surgery once, 16% were operated twice and 1 patient was operated three times. An average of 1.1 surgeries were performed per patient in the congenital group and 1.2 in the acquired group. In both groups, in all diagnostic positions of gaze, the mean preoperative vertical deviation in patients operated twice was found to be significantly greater than in patients operated once. There was no such relationship found for excyclotorsion. In both groups high and statistically significant correlation was found between the amount of vertical deviation and excyclotorsion before treatment and their reduction in the inferior oblique muscle recession group. For the superior oblique muscle tuck, such a relationship was found only in the acquired group. For both groups (congenital and acquired) recession of the inferior oblique muscle was found to be more effective than superior oblique muscle tuck in the reduction of vertical deviation and excyclotorsion for primary position, downward gaze and downward gaze in adduction. Only in upward gaze in adduction the superior oblique muscle tuck, proved to be more effective than inferior oblique muscle recession. Hypercorrection (vertical and torsional) was found only in the upper field of binocular gaze. Postoperative Brown’s syndrome was found to be more frequent after a superior oblique muscle tuck than after recession of the inferior oblique muscle. The risk of postoperative Brown’s syndrome after the superior oblique muscle tuck was particularly high in the congenital group. Conclusions: Recession of the inferior oblique muscle was found to be not only more effective but also safer than superior oblique muscle tuck.